2004
DOI: 10.1093/intqhc/mzh006
|View full text |Cite
|
Sign up to set email alerts
|

Meeting patient's expectations in primary care consultations in Lithuania

Abstract: The most frequently reported expectations on the Patient Intentions Questionnaire were for "getting information" and "understanding and explanation" of the patients' health problem items, and the least mentioned were for emotional support items. Patients with more expectations met were found to have significantly higher scores on the satisfaction index. Satisfaction with the consultation is best predicted by meeting the patient's expectations for understanding and explanation, and for emotional support. Provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 22 publications
6
35
0
6
Order By: Relevance
“…Patients consider nurses' attitudes and behaviors as one of the most important criterion to assess the quality of health care services. 17,18 The expectations of patients in respect to personal rights, good communication and attention, clean and safe environment and a qualitative service consist of basically the attitude and behaviour that are relevant to the purpose of patients rights.…”
Section: Discussionmentioning
confidence: 99%
“…Patients consider nurses' attitudes and behaviors as one of the most important criterion to assess the quality of health care services. 17,18 The expectations of patients in respect to personal rights, good communication and attention, clean and safe environment and a qualitative service consist of basically the attitude and behaviour that are relevant to the purpose of patients rights.…”
Section: Discussionmentioning
confidence: 99%
“…140,143,233,236 Some studies, however, have reported that fulfilment of patients' expectations accounts for no more than one-quarter of the variance in patients' satisfaction. 152 Rao et al 138 undertook a review of the expectancy literature based on MEDLINE 1966-99. They reported confusion in the literature between expectation fulfilment and satisfaction, and commented on the narrowness of all studies included (frequently based on single visits).…”
Section: Expectancy Itemsmentioning
confidence: 99%
“…In sub-Saharan Africa, hypertension has emerged as a major public health concern due to rural-urban migration coupled with modernisation trends, which are characterised by sedentary lifestyles and consumption of food rich in refined carbohydrates and animal fat. 11 It is estimated that over 20 million people in the region are affected by hypertension 8 and the prevalence has been reported to be on the increase in recent years because of the aforementioned factors.…”
Section: Introductionmentioning
confidence: 99%
“…10 The bio-psychosocial model of care seeks to understand these social, cultural and psychological aspect of the patient through the use of the Fear, Ideas, Function, and Expectation (FIFE) family tool, which was developed specifically for use in primary care. 11 The understanding of the psychosocial perspective is very in important in the management of chronic illness like hypertension as patients have to live with the disease for the rest of their lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation